A study of the microstructural characteristics of dental amalgams - Acciari, H. A. [UNESP]; Codaro, E. N. [UNESP]; Guastaldi, Antonio Carlos [UNESP] (Transtec Publications Ltd, 1999)
Metallographic studies by scanning electron microscopy and energy dispersive spectroscopy carried out for two types of dental amalgam showing a porous multiphase material. Surface analysis shows that the structure of the Dispersalloy amalgam consists of gamma-Ag3Sn, gamma(1)-Ag2Hg3, eta'-Cu6Sn5, epsilon-Cu3Sn and eutectic Ag-Cu phases. while Velvalloy amalgam consists mainly of gamma, gamma(1) and gamma(2)-Sn7-8Hg phases. The latter phase presents an uniform distribution often associated with voids.
Keywords: amalgam; dental amalgam alloys; silver-based alloy